Purification and characterization of the extracellular C3d-binding protein of Candida albicans. - Saxena, A (1990)
A C3d-binding glycoprotein was purified from the culture filtrate of Candida albicans by preparative isoelectric focusing. The protein possessed a pI of 3.9 to 4.1 and could inhibit rosetting of EAC3d (sheep erythrocytes conjugated to C3d) by pseudohyphae of C. albicans. When analyzed by polyacrylamide gel electrophoresis in the presence of sodium dodecyl sulfate and mercaptoethanol, the protein migrated as a doublet with apparent molecular masses of 55 and 60 kilodaltons (kDa) and as a 50-kDa band in nonreducing gels. These results were observed with Aurodye stain for proteins. Western immunoblot, and concanavalin A stain, which indicates that both bands contain carbohydrate as well as antigenic determinants. The treatment of purified glycoprotein with endoglycosidase F but not endoglycosidases H, N, and O resulted in a complete conversion of the doublet into a faster-migrating broad band with an apparent molecular mass of 45 kDa. When the amino acid analysis of the C3d-binding protein was compared with that of the CR2 from B lymphocytes, significant differences were observed. These data indicate that C. albicans secretes a C3d-binding protein during growth in vitro which appears to be different from the mammalian C3d receptor.